Plant Hormonomics: Multiple Phytohormone Profiling by Targeted Metabolomics - Šimura, Jan; Antoniadi, Ioanna; Široká, Jitka; Tarkowská, Danuše; Strnad, Miroslav; Ljung, Karin; Novák, Ondřej (Plant physiology, 2018)
Phytohormones are physiologically important small molecules that play essential roles in intricate signaling networks that regulate diverse processes in plants. We present a method for the simultaneous targeted profiling of 101 phytohormone-related analytes from minute amounts of fresh plant material (less than 20 mg). Rapid and nonselective extraction, fast one-step sample purification, and extremely sensitive ultra-high-performance liquid chromatography-tandem mass spectrometry enable concurrent quantification of the main phytohormone classes: cytokinins, auxins, brassinosteroids, gibberellins, jasmonates, salicylates, and abscisates. We validated this hormonomic approach in salt-stressed and control Arabidopsis (Arabidopsis thaliana) seedlings, quantifying a total of 43 endogenous compounds in both root and shoot samples. Subsequent multivariate statistical data processing and cross-validation with transcriptomic data highlighted the main hormone metabolites involved in plant adaptation to salt stress.
Keywords: Plant Shoots; chemická frakcionace; Chromatography, Liquid; Metabolomics; Salt Stress; Arabidopsis; metabolomika; výhonky rostlin; tandemová hmotnostní spektrometrie; Plant Roots; regulátory růstu rostlin; reprodukovatelnost výsledků; chromatografie kapalinová; Reproducibility of Results; kořeny rostlin; Plant Growth Regulators; Chemical Fractionation; Tandem Mass Spectrometry; solný stres